Setor sucroenergético: uma análise sob o tripé da sustentabilidade - VERRI, Reginaldo Aparecido (2016)
The sugar and alcohol production, since the harvest of sugar cane to the sugar and bioethanol production was the objective of this project that sought the three pillars of sustainability in a power plant, located in the northuest of the State of Paraná. The methodology was qualitative / quantitative, with exploratory and field research with documentary data collection, halfstructured interview and observation technique. The results show that the sector has the potential of practices based on sustainable development and that these are embodied in the corporate governance policies of the company. The economic pillar has proven business performance with reductions in operating costs, regional personal workforce, increased productivity and use of precision agriculture. It was seen the social inclusion of workers with professional qualifications and residences program. Environmentally, a renewable energy matrix, with evolution of the cane cutting, from burning to the mechanized, which reduces the emission of CO2 in the atmosphere. Also, the electricity generation from bagasse. These initiatives gave environmental certificates to the sugar- alcohol unit, which attest its concern with the sustainability.